Assisted Hatching Treatment of Piezo-Mediated Small Hole on Zona Pellucida in Morula Stage Embryos Improves Embryo Implantation and Litter Size in Mice - Hao, Xin; Zhao, Yi-Tong; Ding, Kang; Xue, Fang-Rui; Wang, Xin-Yu; Yang, Qi; Han, Zhe; Liang, Cheng-Guang (Frontiers in Cell and Developmental Biology, 2021)
For in vitro produced embryos generated from IVF or ICSI procedure, the intra- and extra- environmental factors during in vitro culture have significant impact on latter embryo development and fetus growth. Assisted hatching (AH), an effective approach to facilitate hatchability for in vitro generated embryos, is an essential step for successful embryo implantation in uterus. However, regarding to different AH methods reported in clinical practice, it is still unknown whether zona pellucida (ZP) broken based AH applied in diverse stages of embryos affect implantation and foetal development. Here, piezo-mediated AH treatments were classified into four categories: (1) drilling one small hole with diameter of 10 μm on ZP (Small Hole, SH); (2) drilling one large hole with diameter of 40 μm on ZP (Large Hole, LH); (3) made a small area with diameter of 40 μm thinner on ZP (Small area Thinner, ST); (4) made a large area with diameter of 80 μm thinner (Large area Thinner, LT). These four AH treatments were applied in different stage embryos including 2-cell, 4-cell and morula. The most efficient AH approach was chosen according to the final hatch rate at 120 hours after fertilization. We found that the approach of SH applied in morula stage embryos obtained the highest hatch rate. To further investigate if this treatment has any side effect on later development after embryo transfer, we evaluated embryo implantation, gestational period, litter size and growth. Our results showed that SH applied in morula stage embryos could facilitate the implantation process, increase litter size. Meanwhile, this approach had no side effect on birth weight, growth, or gender ratio in the offspring. We conclude that drilling a small hole on ZP in morula stage embryos is an effective and reliable assisted hatching approach for in vitro cultured embryos in rodent. And this approach is worth further investigating in human-assisted reproductive technology.